The tandem-repeat polymorphism of the DC-SIGNR gene does not affect the susceptibility to HIV infection and the progression to AIDS - Lichterfeld, Mathias (Clinical immunology (Orlando, Fla.), 2003)
DC-SIGNR is a C-type lectin that functions as a transreceptor for HIV-1. The exon 4 of the DC-SIGNR gene comprises a variable number of 69-bp tandem repeats, encoding for parts of the extracellular protein domain. Here, we analyzed the relevance of this gene polymorphism for the interindividual transmission of HIV-1 and the progression to AIDS. A cross-sectional comparison between HIV-1-infected patients (n = 391) and healthy volunteers (n = 134) did not reveal significant differences with regard to the DC-SIGNR allele distribution. Moreover, DC-SIGNR allele frequencies were similar in slowly progressing HIV patients (n = 31) and patients who rapidly progressed to AIDS (n = 46). Additionally, in a cohort of 149 newly HIV-infected patients, no relationship was found between HIV set point viremia and DC-SIGNR genotypes. Thus, the DC-SIGNR tandem-repeat polymorphism in exon 4 does not have a significant impact on the host's susceptibility to HIV and the clinical progression to AIDS